Participant evaluations of the FUEL intervention designed for female endurance athletes at risk of REDs - Solstad, B. E.; Lysdahl Fahrenholtz, I.; Melin, A.; Garthe, I.; Klungland Torstveit, M. (Sports Psychiatry, 2025)
Abstract:Introduction: Based on a mixed methods design, we investigated the experiences and evaluations of female endurance athletes at risk of REDs who participated in the FUEL intervention programme. Methods: Eighty-two percent of the FUEL participants filled out an evaluation questionnaire, and ten participated in a semi-structured interview. The quantitative data were analysed using a Bayesian Mann-Whitney test, while a critical realist approach was used to analyse the qualitative data. Results: The overall satisfaction rate (from 1 to 10) was 9.1 ± 1.1, with weak evidence for a higher satisfaction level among the FUELcombined (16 digital lectures and 8 individual consultations) compared to FUELlectures (16 digital lectures) participants (9.3 ± 0.9 versus 8.0 ± 1.5, BF10=1.00). Most of the participants found the duration and frequency of the consultations appropriate and did not find the digital format limiting. These results were supported by the qualitative findings showing that the participants expressed educative and motivating experiences. They also appreciated the 16-week intervention duration providing the opportunity to absorb new knowledge, implement it in their daily routines, become more body conscious, and reflect on their new positive bodily experiences. Conclusion: The participants in this multicenter study were satisfied with the FUEL intervention expressing their intentions to recommend it to other athletes and their entourage. They also highlighted the time given to acquire new knowledge, being able to reflect on their positive bodily experiences, and positively change their mindsets. Our findings may be of value for future studies developing highly needed sports nutrition interventions for the prevention of REDs at all levels.